The Cantomanyog Zone of Peace the role of the grassroots church in local peacemaking. [article]. - Briones, Alfredo V.
The role of the grassroots Church of Basic Electrical Community(BEC)in a local peacemaking was the context of the protracted war between the Philippine government the New People's Army(NPA). This study looked into the political psychological variables that may have contributed to the local peacemaking process, the shifts in the predisposition of key actors, and the transformation of the community's social organizational structures and interpersonal interaction of its members. The theoretical assumption was based on Greenstein's (1992) comprehensive map for the analysis of personality and politics. The participants were mostly the residents of the zone of peace(ZOP) community in Sitio Cantomayog, Candoni, Negros Occ. The descriptive research design was still utilized. The qualitative data were subjected to content analysis. The result showed that the political psychological variables were the BEC formation and orientation of the local community, the impact of violence in their lives, leadership style, the emphasis on collective decision making, and the cognizance of being empowered. Peacemaking behaviors of key actors modified the community's social organizational structures and emphasized closer interpersonal interactions that , in turn further reinforced such behaviors. Salient among these behaviors are the residents' respect for reflection and process, participatory decision making, promotion of positive values, spiritual moral integrity , deep awareness of divine presence, and a perspective of the ZOP as a legacy to future generations. These findings are congruent with the study's theoretical framework. In conclusion, policy recommendations are proposed for the government and for the Catholic Church.